2008
DOI: 10.1186/1742-6405-5-21
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvements in self-reported gastrointestinal tolerability, quality of life, patient satisfaction, and adherence with lopinavir/ritonavir tablet formulation compared with soft gel capsules

Abstract: Background: The tablet formulation of ritonavir-boosted lopinavir (LPV/r; Kaletra ® ) has many advantages over the soft gel capsule (SGC) formulation, including lower pill count, no refrigeration requirement, and no dietary restrictions. These advantages may help improve patient compliance and therefore increase adherence to treatment. However, there are limited data regarding patient preferences and only recently was the comparative efficacy and tolerability data of LPV/r SGC versus tablet formulation present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Data from this study are consistent with previous studies that demonstrated patient preference for the tablet formulation after switching from the SGC. 14,20,21 Plasma concentrations for TG, LDL, and HDL cholesterol were similar for both the once-daily-dosed and twice-daily-dosed LPV/r groups throughout the study. TC:HDL and LDL:HDL ratios were similar in both groups and decreased slightly through 48 weeks compared with baseline.…”
Section: Discussionmentioning
confidence: 94%
“…Data from this study are consistent with previous studies that demonstrated patient preference for the tablet formulation after switching from the SGC. 14,20,21 Plasma concentrations for TG, LDL, and HDL cholesterol were similar for both the once-daily-dosed and twice-daily-dosed LPV/r groups throughout the study. TC:HDL and LDL:HDL ratios were similar in both groups and decreased slightly through 48 weeks compared with baseline.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are consistent with 3 studies evaluating quality of life, tolerability, and satisfaction in patients who were switched from the SGC to the tablet formulation. 11,24,25 Diarrhea has been associated with increased health care costs, lost work days, need for assistance with care, and is a negative predictor of survival. [26][27][28] In a prospective caseÀcontrol study of 192 HIV-infected participants with and without diarrhea, MOS-HIV quality-of-life scores were significantly higher in all domains for participants without diarrhea (average differences ranged from þ8 for physical and cognitive functioning to þ19 for social functioning) and significantly associated with diarrhea severity.…”
Section: Discussionmentioning
confidence: 99%
“…10 Limited clinical reports suggest that the LPV/r meltrex tablets may be associated with improved tolerability and quality of life. 6,11 Monotherapy with RTV-boosted PIs has been investigated in a variety of treatment strategies. 12 Monotherapy has potential advantages of reduced drug-associated toxicity, drug interactions, pill count, and cost, although it currently cannot be routinely recommended with the information to date.…”
Section: Introductionmentioning
confidence: 99%
“…Lopinavir capsules received approval in 2000 as a twice-daily regimen. Subsequently, the capsules were replaced by pills that were better tolerated and did not require dietary restrictions or Handbook of Antimicrobial Resistance DOI 10.1007/978-1-4939-0667-3_28-1 # Springer Science+Business Media New York 2014 refrigeration (Schrader et al 2008). Efficacy of lopinavir/ritonavir as initial therapy was compared in a randomized placebo controlled study with nelfinavir (three times a day) as comparator with an NRTI backbone in both arms.…”
Section: Second-generation Protease Inhibitor Therapy; Boosting Of Prmentioning
confidence: 99%